Distribution of Total Volatile Organic Compounds at taxi drivers in Tehran - Seyyed Mohammad Javad Golhosseini; Hossein Kakooei; Seyyed Jamaleddin Shahtaheri; Mansour Rezazadeh Azari; Kamal Azam (Iranian Journal of Health, Safety and Environment, 2015)
Air pollution is currently the most serious environmental health threat worldwide. Volatile Organic Compounds (VOC) are considered as the main effective factors in causing air pollution. Vehicles are among the major sources which emit these compounds, so it seems that automobiles' microenvironment is one of the places where people are exposed to high concentration of VOC. Evaluating the exposure amount of Total Volatile Organic Compounds (TVOC) can indeed be used as an indicator to estimate the amount of exposure to every individual VOC. This study was conducted on the concentration of TVOC inside Tehran taxies for a period of one year. For this purpose, a real time instrument equipped with photo-ionization detector (PID) was used. Consequently, the highest and the lowest measured TVOC in taxies equaled 3.33 ppm and 0.72 ppm, respectively. In addition, the arithmetic mean of TVOC concentration was 1.77±0.53 ppm inside the examined taxies. In this study, the parameters like measurement time, climate and vehicle conditions were found to have significant effect on the amount of exposure to TVOC.